1973
DOI: 10.1139/v73-045
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Rhenium β-Diketone Complexes. III. The Crystal and Molecular Structure of Bis(μ-O-1,3-diphenylpropane-1,3-dionatotricarbonylrhenium(I))

Abstract: One of a series of compounds obtained by the reaction of chloropentacarbonylrhenium (1) with [3-diketones has been shown by single crystal X-ray diffraction to be bis(p-0-1,3-diphenylpropane-1,3-dionatotricarbonylrhenium(1)f. The crystals are monoclinic with lattice parameters a = 11.988(A) A, b = 14.441(9) A, c = 10.298(7) A, = 115.25(7)'. The space group is PZ,!c and there are two dimers per unit cell. A total of 1563 independent reflections were measured on a single crystal X-ray diffractometer and the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…An M-X bond, where X has some K-acceptor properties, trans to an olefinic group substituted with electron-withdrawing ligand, (C(B)), should be longer than a similar bond trans to an unsubstituted olefinic 'group, (C(A)), because in the competition for d-K electrons, the increased K-back bonding to the olefin would weaken the trans K-bond (9). We have shown previously that P-ketoenolates in low valence compounds of rhenium were K-acceptors (22), and that when P-ketoenolate oxygen atoms were trans to a group with good K-acceptor ability (CO) the Re-0 distance was larger than normal (23). Further, Mason and Tow1 (lo), have suggested that, for a system L-M-X, a strong L-M bond caused the M-X bond to become more ionic, and weaker, giving rise to localization of negative charge on X.…”
Section: Discussionmentioning
confidence: 99%
“…An M-X bond, where X has some K-acceptor properties, trans to an olefinic group substituted with electron-withdrawing ligand, (C(B)), should be longer than a similar bond trans to an unsubstituted olefinic 'group, (C(A)), because in the competition for d-K electrons, the increased K-back bonding to the olefin would weaken the trans K-bond (9). We have shown previously that P-ketoenolates in low valence compounds of rhenium were K-acceptors (22), and that when P-ketoenolate oxygen atoms were trans to a group with good K-acceptor ability (CO) the Re-0 distance was larger than normal (23). Further, Mason and Tow1 (lo), have suggested that, for a system L-M-X, a strong L-M bond caused the M-X bond to become more ionic, and weaker, giving rise to localization of negative charge on X.…”
Section: Discussionmentioning
confidence: 99%
“…A calculation, assuming the P-diketone- P-diketone contacts were greater than twice the carbon van der Waals radius, and based on the geometries determined previously (12,13), showed that for cis-Re,(CO),dik, the P-diketone plane would be bent about 55" from the OReO plane (cf. the previous highest value of 34" (12)) and thus would make the ReOC angles about 100 and 80", far smaller than any previously reported value for MOC angles in metal P-ketoenolate complexes.…”
Section: Fig 1 the Molecular Structures Of Rez(c0)6dikz And Re(co)mentioning
confidence: 95%